Awareness on the Methods to Overcome Depression among Undergraduate Students in An University Hospital Setting - Hiranya.S1 , V.Vishnu Priya2 , R.Gayathri3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Depression is a mental disorder characterized by persistent depressed mood , loss of interest in activities,significant impairment in daily life .It is a mood disorder of feelings of sadness,loss of anger and interferein people’s life activitiesThis is a prospective observational study .A well structured questionnaire isadministered through online google forms link.This study is approved by the scientific review board ofSaveetha Dental College. From the data statistics using SPSS, 67% were aware of methods to overcomedepression, 34% felt behavioural changes is a symptom of depression, 27% agreed eating disorder is asymptom for depression and 8% agree that insomnia was a symptom for depression. The association betweengroups was assessed by Chi Square test where p < 0.05 was considered statistically significant. We haveobserved that association between gender and responses to awareness on methods to overcome depressionwas statistically significant (p = 0.043 ). From this study we may conclude that many students are awareabout depression and the methods to overcome depression.